A survey of assimilable organic carbon, biodegradable organic carbon and coliform growth response in US drinking waters - Kaplan, L.; Reasoner, D.; Rice, E.; Bott, T. (Revue des sciences de l'eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 1992)
The primary objectives of this study were : 1) to document concentrations of Assimilable Organic Carbon (AOC) in a survey of a broad range of drinking waters and treatment processes; 2) compare the Colilorm Growth Response (CGR) to AOC concentrations; and 3) compare Biodegradable Dissolved Organic Carbon (BDOC) concentrations to AOC concentrations. AOC was measured with mixed cultures of Pseudomonas fluorescens strain P-17 and Spirillum sp. strain NOX. Test waters were transferred to 40-ml vials, pasteurized, inoculated, and incubated at 15°C. Colony forming units was the test parameter. CGR was performed with pasteurized test water inoculated with Enterobacter cloacae. Samples were incubated at 20°C for 5 days and response determined from colony forming units. The BDOC assay was performed in 40-ml vials, with glass fiber filtered, pasteurized test water, inoculated with the indigenous microflore from a stream, and incubated for 28 days in the dark et room temperature. The survey involved 109 samples from 79 drinking water supplies located throughout the United States and Canada, including 26 groundwater and 53 surface water sources. Utility personnel were supplied with sample bottles and instructions for sampling and pasteurtzing the test waters. Pasteurized water was sent to the Stroud Water Research Center for AOC, BDOC, and DOC analyses, and to the Risk Reduction Engineering Laboratory for the CGR assay. Densities of coliforms and heterotrophic plate count bacteria (HPC) were measured in the test waters by utility personnel. DOC concentrations ranged from 203 to 4943 µg/L. AOC concentrations ranged from 18 to 322 µg/L, or 2.4 % to 44.0 % of the DOC. High pH values in 5 test waters inhibited the growth of both AOC bioassay organisms. BDOC concentrations ranged from 1 to 1521 µg/L, or 0.4% to 52.8 % of DOC. The CGR assay indicated that 79 % of the test waters did not promote coliform growth, 7 % were strongly growth promoting, all from surface water sources, and 14 % were moderately growth promoting. No coliforms and only low densities at HPC organisms were reported by utilities for treatment plant effluents. The correlation of AOC and BDOC was significant (P≪0.01), with a correlation coefficient of r=0.594. Significant correlations were also found for AOC and DOC, and BDOC and DOC. Correlations of CGR and either AOC or BDOC were not statistically significant.